Courtship, marriage and family in Sarawak - Hew, Cheng Sim (Universiti Malaysia Sarawak (UNIMAS), 2013)
Sarawak’s population of 2.4 million consists of the Iban, Chinese, Malay, Bidayuh, Orang Ulu and Melanau in that order of demographic size. The classification of Orang Ulu alone includes the Kayan, Kenyah, Kelabit, Lun Bawang, Punan, Penan, Murut, Kedayan and a host of other smaller communities. It is said that there are at least 27 different ethnic groups but no one is really sure1 The complexity of such a multiethnic population has led some to say that Sarawak is an anthropologist’s paradise or nightmare depending on how one looks at it. It has a rich history of research where anthropologists documented the indigenous cultures and customs dating back to pre colonial times. As a result, we have much historical information on the family and kinship structures of the various indigenous groups but far less is known of the contemporary family. In this chapter, I have tried to piece together whatever little there is to try to understand the changes that have occurred. In order to do this, we have to begin with the past. Although I have set up the following sections as a contrast between the past and the present, it is more accurate to talk of continuity and change. Present day Sarawak, is after all a land which encompasses the full range of communities from the nomadic hunter-gatherer Penan in the hinterland to the globetrotting elites in the cities. It is therefore not my intention to present a dichotomous view but merely as a comparative especially in the light of rapid socio-economic transformation in Sarawak. However, the focus of my discussion of the past would be on the indigenous communities in rural Sarawak.